The Estimation of Knowledge Solidity Based on the Comparative Analysis of Different Test Results - Y. K. Khenner; T. S. Oznobikhina (Образование и наука)
At present, the testing techniques of knowledge estimation are widely spread in educational system. However, this method is seriously criticized including its application to the Unified State Examinations. The research is aimed at studying the limitations of testing techniques. The authors recommend a new way of knowledge solid- ity estimation bases on the comparative results analysis of various kinds of tests. While testing the large group of students, the authors found out that the results of the closed and open tests substantially differ. The comparative analysis demonstrates that the open tests assessment of the knowledge solidity is more adequate than that of the closed ones. As the research is only based on a single experiment, the authors recommend using this method further, substantiating the findings concerning the differences in tests results, and analyzing the advantages and disadvantages of the tests in question.